The Czech phenomenon of men's decathlon development - Wang, Z.; Lu, G. (International Journal of Sports Science and Engineering, 2007)
By means of digital documentary and materials research it involves data of scores of eight Czech men`s decathletes. Based on the data and other relevant references, statistical methods were applied to analyze the characteristics of Czech decathlon in the aspects of selection of athletes, management and training. The results show that Czech decathletes have an outstanding running and jump capability in the early stage; later a large emphasis are put on the balanced development of both strength and technique; large quantity of exercise and training team management are carried out as well. This can also serve as a reference to the development of decathlon in our country.